2008
DOI: 10.1007/s11426-008-0145-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of radionickel sorption on MX-80 bentonite as a function of pH and ionic strength

Abstract: MX-80 bentonite was detected using acid-based titration, XRD and FTIR in detail. The sorption behavior of 63 Ni(Ⅱ) from aqueous solution to MX-80 bentonite was investigated as a function of solid content, ionic strength and pH by using batch technique. The experimental data of 63 Ni(Ⅱ) sorption on MX-80 bentonite was obtained using the diffuse layer model (DLM) with the aid of FITEQL 3.1 program. The results indicated that the sorption of 63 Ni(Ⅱ) on MX-80 bentonite was mainly dominated by surface complexation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Moreover, FTIR peaks at 632 nm are associated to the Al-O connection that was in a tetrahedral coordination with aluminum cations [32]. The FTIR peaks at 527 nm and 460 nm are associated to Al-O-Si and Si-O-Si bending vibrations, respectively [33,34]. Montmorillionite-22A is the main component of bentonite clay.…”
Section: Surface Characterization Of Bentonite Claymentioning
confidence: 99%
“…Moreover, FTIR peaks at 632 nm are associated to the Al-O connection that was in a tetrahedral coordination with aluminum cations [32]. The FTIR peaks at 527 nm and 460 nm are associated to Al-O-Si and Si-O-Si bending vibrations, respectively [33,34]. Montmorillionite-22A is the main component of bentonite clay.…”
Section: Surface Characterization Of Bentonite Claymentioning
confidence: 99%
“…However, the added OH  only changes the pH values in the blank system [24,25]. The potentiometric titrations of intrinsic attapulgite and blank under different ionic strengths are shown in Figure 3.…”
Section: Potentiometric Titrationmentioning
confidence: 99%
“…Figure 4 shows the Gran plots of the back-titration data of blank, intrinsic and activated attapulgite samples. The values of the Gran function (G) were calculated as follows [24,25]:…”
Section: Potentiometric Titrationmentioning
confidence: 99%
See 1 more Smart Citation
“…9, the amount of U(VI) ions adsorbed decreased as the NaNO 3 concentrations increasing from 0.01 to 0.1mol L -1 , and then remained stable when the concentration of NaNO 3 was higher than 0.1 mol L -1 . These results indicated that three kinds of materials are greatly influenced at low ionic strength but weakly influenced at a higher ionic strength [54][55][56]. This phenomenon could be explained by the fact Fig.…”
Section: Effect Of Ionic Strengthmentioning
confidence: 82%